DEVELOPMENT OF URBAN MARKET SPATIAL FOR HIGHEST AND BEST USE OF LAND PRODUCTIVITY AND SUSTAINABILITY - Utomo, Christiono; Rahmawati, Yani; Krestawan, Iman (PLANNING MALAYSIA, 2018)
No less than 40% of around 70 traditional retail markets in Surabaya are located in the downtown area where the economic value of the location is high, but not being optimally utilized. Sustainable planning can be achieved if the area is not only able to stand and grow by itself but also contributes to the economic growth of the region and the surrounding trade. Based on its potential, urban land use is principally needed to be analysed on its capability in producing highest property value. This research develops adaptive and collaborative concepts on spatial configuration design and market economy value in urban area. It is found to be the best regional planning concept to support sustainable economic achievement. It also has the capability in minimizing failure of market development in urban areas as well as supporting success in structuring the city. Triangulation method was applied through qualitative and quantitative approaches, and using Highest and Best Use (HBU) analysis technique. The analysis began with an explorative study to explore alternatives of land use, which was then followed by a 5-stages analysis including determination of alternative use, regulatory compliance and permits, possibility and affordability of construction, financial feasibility, and maximum productivity of land.